Contraception During Perimenopause: Practical Guidance - Grandi G; Di Vinci P; Sgandurra A; Feliciello L; Monari F; Facchinetti F (Dove Medical Press, 2022)
Giovanni Grandi,1 Pierluigi Di Vinci,2 Alice Sgandurra,1 Lia Feliciello,1 Francesca Monari,1 Fabio Facchinetti1 1Department of Medical and Surgical Sciences for Mother, Child and Adult, University of Modena and Reggio Emilia, Azienda Ospedaliero Universitaria Policlinico, Modena, 41124, Italy; 2International Doctorate School in Clinical and Experimental Medicine, Department of Biomedical, Metabolic and Neural Sciences, University of Modena and Reggio Emilia, Modena, 41124, ItalyCorrespondence: Giovanni Grandi, Department of Medical and Surgical Sciences for Mother, Child and Adult, University of Modena and Reggio Emilia, Azienda Ospedaliero Universitaria Policlinico, Via del Pozzo 71, Modena, 41124, Italy, Tel +39 059 422 2665, Email giovanni.grandi@unimore.itAbstract: Climacteric is by no means in itself a contraindication to safe contraception. On the contrary, there are several conditions related to the perimenopause that could benefit from the use of modern contraceptives, mainly hormonal, with the goals of avoiding unintended pregnancies and giving further possible benefits beyond contraception (menstrual cycle control, a reduction of vasomotor symptoms and menstrual migraines, a protection against bone loss, a positive oncological risk/benefit balance). This narrative review aims to provide practical guidance on their possible use in this particular life stage, both short- and long-acting reversible contraceptives, and to assist clinicians for women transitioning from contraception to their menopausal years, including the possible initiation of postmenopausal hormone therapy. Comprehensive contraceptive counselling is an essential aspect of the overall health and wellbeing of women and should be addressed with each such patient irrespective of age.Keywords: contraception, perimenopause, SARCs, LARCs, oral contraceptives, combined oral contraceptives, vaginal rings, patch, intrauterine devices, implants, forties, metabolism